Konsep Bai’ Mabrūr pada Transaksi Barter Petani Garam di Kabupaten Jeneponto - St Nurrahma; Irwan Misbach; Amiruddin K (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2022)
This study aims to analyze the barter transactions of salt farmers and then to elaborate on the concept of bai' mabrūr in transactions carried out by the community in Jeneponto Regency. The research method used is descriptive qualitative method with a sharia economic approach. The results of the study show that salt barter transactions have occurred since ancient times and are still ongoing today. The objects exchanged are basic necessities, such as rice, sugar, coffee and cigarettes. The exchange stage starts with the process of mutual contact between farmers and traders, then the process of negotiation and price estimation. In terms of mabrur or acceptance of barter transactions, the results of these barter transactions are more dominant in terms of the good or the benefits rather than the disadvantages. Salt barter transactions show a form of mutual help for both parties, where traders help farmers in meeting their daily needs and in marketing salt, while from the other side, farmers also help traders in terms of getting salt more easily which is also resold. to get more profit.